2022
DOI: 10.3390/ijms23147677
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Advancement in the Complex Response of Plants to Viroid Infection

Abstract: Viroids are the smallest plant pathogens, consisting of a single-stranded circular RNA of less than 500 ribonucleotides in length. Despite their noncoding nature, viroids elicit disease symptoms in many economically important plant hosts, and are, thus, a class of pathogens of great interest. How these viroids establish disease within host plants, however, is not yet fully understood. Recent transcriptomic studies have revealed that viroid infection influences the expression of genes in several pathways and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…Despite differences in diseases causes by pospiviroids and avsunviroids, the cellular pathways affected in ASBVd-infected avocado were comparable to those observed in other viroid-host interactions. One host pathway where DEGs were commonly observed in viroid-infected hosts was plant immune response ( Joubert et al., 2022 ). In this study we observed the upregulation of 14 PR genes and several different RLK s in infected avocado, suggesting that PTI is induced by ASBVd; this result correlates with the findings of other viroid-host transcriptome studies, which showed that PR genes and RLK s are induced in PSTVd-infected tomato, CEVd-infected ‘Etrog’ citron, and in hop ( Humulus lupulus ) infected with citrus bark-cracking viroid (CBCVd) ( Mishra et al., 2018 ; Wang et al., 2019 ; Więsyk et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite differences in diseases causes by pospiviroids and avsunviroids, the cellular pathways affected in ASBVd-infected avocado were comparable to those observed in other viroid-host interactions. One host pathway where DEGs were commonly observed in viroid-infected hosts was plant immune response ( Joubert et al., 2022 ). In this study we observed the upregulation of 14 PR genes and several different RLK s in infected avocado, suggesting that PTI is induced by ASBVd; this result correlates with the findings of other viroid-host transcriptome studies, which showed that PR genes and RLK s are induced in PSTVd-infected tomato, CEVd-infected ‘Etrog’ citron, and in hop ( Humulus lupulus ) infected with citrus bark-cracking viroid (CBCVd) ( Mishra et al., 2018 ; Wang et al., 2019 ; Więsyk et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…5 a, b & c). These TFs have been shown to regulate components of phytohormone networks, plant immunity, and plant response to stress ( Ambawat et al., 2013 ; Dröge-Laser et al., 2018 ; Sun et al., 2018 ; Yuan et al., 2019 ) and were differentially expressed in several viroid-host interactions studied to date ( Joubert et al., 2022 ). We hypothesise that altered accumulation of TFs in ASBVd-infected avocado may be responsible for downstream effects on host gene expression observed in this study, though the initial mechanism influencing TF expression remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations